Remittances as a Shield to Vulnerable Households in Macedonia: The Case When the Instrument is Not Strictly Exogenous. (8th September 2016) - Petreski, Marjan; Petreski, Blagica; Tumanoska, Despina
Abstract: The objective of this article is to investigate whether remittances sent to Macedonia have a role to play for shielding vulnerable households, by highlighting the importance of a strictly exogenous instrument in an IV context. Results suggest that remittance‐receiving households have, on average, a 20.1 per cent lower vulnerability than non‐receiving ones. However, if one has a reasonable belief that vulnerability and the instrument are determined simultaneously, or are directly correlated due to the existence of a third unobservable factor, then the shielding effect of remittances for vulnerable households remains up to the ninth percentage of direct influence and with a reducing magnitude, and then disappears.